MusE GAs FLOw and Wind (MEGAFLOW) VI. A study of C iv and Mg ii absorbing gas surrounding [O ii] emitting galaxies. Issue 1 (21st May 2021) - Schroetter, Ilane; Bouché, Nicolas F; Zabl, Johannes; Rahmani, Hadi; Wendt, Martin; Muzahid, Sowgat; Contini, Thierry; Schaye, Joop; Schmidt, Kasper B; Wisotzki, Lutz
ABSTRACT: Using the MEGAFLOW survey, which consists of a combination of MUSE and UVES observations of 22 quasar fields selected to contain strong Mg ii absorbers, we measure the covering fractions of C iv and Mg ii as a function of impact parameter b using a novel Bayesian logistic regression method on unbinned data, appropriate for small samples. We also analyse how the C iv and Mg ii covering fractions evolve with redshift. In the MUSE data, we found 215 z = 1-1.5 [O ii ] emitters with fluxes 10^-17 erg s −1 cm −2 and within 250 kpc of quasar sight-lines. Over this redshift path z = 1-1.5, we have 19 (32) C iv (Mg ii ) absorption systems with rest-frame equivalent width (REW) W_r 0.05 Å associated with at least one [O ii ] emitter. The covering fractions of z≈ 1.2 C iv (Mg ii ) absorbers with mean W_r≈ 0.7 Å (1.0 Å), exceeds 50 per cent within 23^+62_-16 (46^+18_-13 ) kpc. Together with published studies, our results suggest that the covering fraction of C iv (Mg ii ) becomes larger (smaller) with time, respectively. For absorption systems that have C iv but not Mg ii, we find in 73 per cent of the cases no [O ii ] counterpart. This may indicate that C iv comes from the intergalactic medium (IGM), i.e. beyond 250 kpc, or that it is associated with lower mass or quiescent galaxies.